Relationship between Lichen Planus and Helicobacter pylori Infection - Ali Taghavi Zenouz; Masoumeh Mehdipour; Mohammad Jafari Heydarlou; Narges Gholizadeh (Tabriz University of Medical Sciences, 2010)
Background and aims. Lichen planus (LP) is a relatively common, chronic dermato-mucosal disease that often affects the oral mucosa. Among bacterial infections affecting LP, Helicobacter pylori has recently been proposed as an important etiologic factor. The present study was designed to evaluate the association of LP and H. pylori infection. Materials and methods. This study included 30 patients with skin LP, 30 patients with oral LP and 30 healthy individuals without LP as control group. Patients and control group were selected from those referred to a dental and a dermatology clinic. Urea breathing test (UBT) was performed for all subjects. Descriptive statistic (frequency and percentage) were applied and chi-square test was employed to compare mean differences, using SPSS 13.0 computer software. Results. UBT test were positive in 24 patients (80%) in oral LP group, 22 patients (73.3%) in skin LP group, and 20 individuals (66.7%) in the control group. No significant differences were found in the positive test results between the three groups (P = 0.50). Conclusion. In this study, no significant association was found between LP and H. Pylori infection